Long term follow-up of women treated for screen detected atypical ductal hyperplasia or lobular neoplasia in a large UK screening centre - Brown, Nicole L.; Pritchard, Susan; Harkness, Elaine F.; Lim, Yit; Gandhi, Ashu; Evans, Dafydd Gareth; Howell, Anthony; Howell, Sacha J. (BJC reports, 2024)
Background Atypical ductal hyperplasia (ADH) and lobular neoplasia (LN) increase subsequent breast cancer (BC) risk. However, optimal surveillance and risk reduction regimes remain uncertain. We report management and outcomes of women with ADH and LN to provide data on potential screening/prevention strategies. Methods Women diagnosed with screen detected ADH and/or LN between 2010-2018 at our institution were identified and demographic data, MDT decisions and BC diagnoses extracted from electronic patient records in 2019 and 2023. Results Of 107 women, 74 were discharged to the NHS Breast Screening Programme and 33 were offered enhanced screening (ES). The proportion offered ES increased significantly over time ( p = 0.037). 15/105 (14.3%) developed BC (median follow-up 117 months), 9 screen-detected and 6 symptomatic, with 3 interval cancers diagnosed 12–25 months following their last screen. 3/15 were lymph node positive and 13/14 invasive cancers were estrogen receptor (ER) positive. BC incidence rate was 1499.6/100,000 women/year (SIR = 4.7), lower in the first 5 years of follow-up compared with post 5 years. Conclusions In women with ADH/LN most BCs occur beyond 5 years. ES regimens should therefore extend to at least 10 years and be at least biennial. Preventative therapy should be considered given the high BC SIR and ER positivity of subsequent tumours.